Examining the status of school improvement program implementation in primary schools: a case study in South Ethiopia region - Shanko, Solomon Sapo; Kabtyimer, Muluken Tesfaye (Frontiers in Education, 2024)
The implementation of a School Improvement Program (SIP) is a means to enhance the overall quality of education and ultimately improve students' academic outcomes. Hence, this study aimed to investigate the extent of SIP implementation with respect to its main domains in primary schools of Gamo Gofa Zone, South Ethiopia Region. Accordingly, the current study focuses on four key areas in schools, which include teaching-learning, school leadership and management, parent-community school relations, and healthy school environment. A descriptive survey research design was used with a quantitative research method. From 16 primary schools; 99 teachers, 32 principals, 44 school improvement committees and 396 students were selected using a simple random sampling technique. The research utilized close-ended questionnaires and document reviews as data-gathering instruments. Quantitative data were analyzed using mean, standard deviation, and one-way ANOVA, while qualitative data were analyzed using descriptive narration. The findings revealed that the implementation of SIP in the four main domains was moderate status. However, the domains of teaching-learning and school leadership exhibited a high level of implementation. The study also identified significant differences among districts regarding the extent of implementation in the teaching-learning and community participation domains. Moreover, the results of grade four zonal and grade eight regional examinations indicated that SIP is not yet properly implemented and needs high consideration. Therefore, raising awareness about the revised school improvement Blueprint and framework through short-term training, establishing an incentive system to encourage best practices and implementing formal monitoring and evaluation tools are suggested to boost the status of SIP implementation in the study area.